PRESTASI MAHASISWA DAN PERBANDINGAN KURIKULUM 2013 MENJADI KURIKULUM MERDEKA - Rifka Arifatul Choridah; Nuril Mufidah (Institut Pendidikan Tapanuli Selatan, 2024)
This study aims to analyze the comparison of the 2013 curriculum and the independent curriculum in developing student achievement in the Arabic Language Study Program at UIN Malang. The research method used is qualitative with an analytical descriptive approach. With the subject of Arabic Language Education Study Program students. Data collection techniques were observation and documentation from the 2013 curriculum implementation guidebook, the UIN Malang MBKM guidebook, and the Student Achievement Report Book of the Arabic Language Education Study Program, UIN Malang. As well as doing critical analysis of these data. The results of the research are as follows: 1. During the period when the 2013 curriculum was implemented, namely 2017 – 2020, 47 achievements were reported for students of the Arabic Language Education Study Program. With details, 3 international achievements, 37 national achievements, and 7 regional achievements. 2. During the period when the independent curriculum was implemented, from 2021 to 2023 in June, 59 achievements were reported for students of the Arabic Language Education Study Program. With details, 18 international achievements, 35 national achievements, and 6 regional achievements. 3. Comparison of the efficiency of the 2013 curriculum and the independent curriculum in developing student achievement in the Arabic Language Education Study Program experienced an increase in the period when the independent curriculum was implemented. It should be noted that the independent curriculum will still be implemented for the next period, so it cannot be denied that student achievement is likely to increase.